Hardware implementation of optical switching node for data center networks. Issue 3 (29th November 2018) - Mishra, Shivam; Yadav, Vikas; Hemanth, C.; Sangeetha, R. G.
Abstract: In high performance data center networks, switching the data from source node to destination node needs a proper signal processing to decode the address bits and switch the data and to avoid contention. In this article, we propose the hardware design for switching the data from one node to other bi‐directionally. The design is verified in an experimental test bed.